Wind-induced sound source mapping on Volvo V70 - Ze, Zhang (My University, 2015)
The project is aimed to gain a better understanding of the possibilities and limitations of various sound source measuring technologies including beamforming and Equivalent Source Method (ESM) in aerodynamic noise measurement on a car. It was shown that ESM method has a better resolution for sound source localization at low frequencies and recommended to use for the next coming projects. Subsequently tools like intensity probe and 3D acoustic camera that use aforementioned technologies are then utilized to identify and analyse sound source both inside and outside a Volvo V70. Various configurations with changes at the regions of interests have been tested out, some of which are A-post, rear view mirror, cowl cavity, etc. Afterwards the results are postprocessed, analysed and compared with CFD simulations from Ansys Fluent. Furthermore, a coherence analysis between exterior sound and interior sound is conducted and most influential exterior sound source to the inside noise level is determined. It was shown that mid to low frequency noise sources are the main contributors to interior noise. The low frequency noise is caused by wheelhouse and air flushing on the side window from rear view mirror. The mid frequency noise is from A-post and cowl cavity.
Keywords: Energi; Transport; Grundläggande vetenskaper; Hållbar utveckling; Strömningsmekanik och akustik; Energy; Transport; Basic Sciences; Sustainable Development; Fluid Mechanics and Acoustics